How to Reduce 3-deoxyglucosone and Acetaldehyde in Peritoneal Dialysis Fluids - Zimmeck, Thomas; Tauer, Andreas; Fünfrocken, Michael; Pischetsrieder, Monika (Peritoneal Dialysis International, 2002)
◆ Objective: 3-Deoxyglucosone (3-DG) and acetaldehyde were found to be the major reactive carbonyl compounds in conventional heat-sterilized peritoneal dialysis fluids (PDFs). The aim of this study was to identify factors in the production of PDFs promoting or inhibiting the formation of acetaldehyde and 3-DG. ◆ Design: Single-chamber bag PDFs with different buffer systems and pH values were analyzed for acetaldehyde. 3-Deoxyglucosone was determined in double-chamber bag PDFs with different pH values, in commercially available samples, and in double-chamber products stored under defined conditions. ◆ Results: Acetaldehyde was found in the presence of lactate and malate, whereas in 2-hydroxybutanoate-buffered solution propionaldehyde was detected instead. Between pH 5.0 and 6.0 the acetaldehyde content in lactate-buffered solutions increased strongly.The concentration of 3-DG in the chamber containing glucose in double-chamber bags increased between pH 3.0 and 5.0 by a factor of 6.3-Deoxyglucosone concentrations in commercially available products vary greatly, reflecting the different pH values of these products. A time- and temperature-dependent reaction leads to a reduction in 3-DG and an increase in 5-hydroxymethyl-furan-2-carbaldehyde during storage. ◆ Conclusion: Acetaldehyde is produced by a reaction that requires both lactate and glucose. Thus, its formation can be prevented by a separation of the reaction partners, glucose and lactate, in a double-chamber bag. In double-chamber bags, pH greatly influences the formation of 3-13G. Minimal formation is observed in the region of pH 3.0. This finding should be taken into account for the development of new double-chamber bag PDFs.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.howtor
Keywords: 3-deoxyglucosone; Acetaldehyde; Chemical analysis; Glucose degradation products; Lactate buffer; Peritoneal dialysis fluids